LEVERAGING ORGANOID TECHNOLOGIES TO CHARACTERIZE DYNAMIC TUMOR CELL STATES DRIVING TREATMENT RESISTANCE IN PANCREATIC CANCER (European Journal of Histochemistry)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by a pronounced inter- and intra-tumoral heterogeneity, which fuels chemoresistance and contributes to high mortality rates. Previously, we have developed a branched organoid system embedded in collagen matrices that robustly recapitulates the phenotypic heterogeneity seen in both murine and human PDAC1,2. These organoids display complex, self-organized branching morphogenesis and give rise to distinct, spatially ordered tumor cell populations that reflect their underlying molecular profiles and differentiation states. Importantly, we show that the observed heterogeneity is not random but governed by defined transcriptional programs, particularly epithelial-to-mesenchymal plasticity, that drive the emergence of discrete tumor-cell states. Using integrated phenotypic and transcriptomic profiling, we map this diversity to specific biological functions in vivo, demonstrating that each organoid phenotype corresponds to a tumor-cell state with unique metastatic potential, and therapeutic vulnerabilities. Moreover, we identify dynamic, treatment-induced phenotype reprogramming events that are targetable, paving the way for rational design of state-specific therapeutic interventions. Building on our findings, we are now focusing on elucidating intra-organoid heterogeneitysuch as tip–trunk hierarchies at the single-cell level, to uncover the mechanisms of self-organization and to determine how distinct organoid phenotypes and subpopulations contribute to liver metastasis and treatment resistance. In summary, we have established a scalable and mechanistically informative organoid platform that enables in vitro modeling of PDAC heterogeneity. This system provides a framework for dissecting the tumor cell–intrinsic drivers of phenotypic plasticity and for developing phenotype-guided treatment strategies aimed at overcoming resistance and improving patient outcomes.